Sharing travel related experiences on social media – integrating social capital and face orientation - Kumar, Thivashini B Jaya; Goh, See-Kwong; Balaji, M.S. (SAGE Publications Ltd, 2020)
Tourists can share their travel experiences or related information freely through social media platforms. The purpose of this research is to explore the factors associated with sharing travel related experiences on social media by travellers in the context of social capital theory and person-context interaction theory. Data were collected among consumers in Malaysia using a structured survey; 423 responses were generated. The findings show that the social capital dimensions (social ties, trust, reciprocity and shared vision) positively impact sharing intention on social media while identification doesn’t impact the sharing intention. The results also partially support the hypothesis that protective face orientation negatively influences social capital dimensions and sharing intention while acquisitive face orientation positively influences them. The authors shed light on the construction of social capital dimensions and face orientation and the relative importance of the sharing intention on social media.